Ethanol as a solvent and hot extraction technique preserved the antioxidant properties of tamarind (Tamarindus indica) seed - Yeasmen, Nushrat; Islam, Md. Nazrul (Journal of Advanced Veterinary and Animal Research, 2015)
The influence of two extraction solvents (ethanol and acetone) and two extraction techniques i.e., hot extraction at 400C and cold extraction at 260C were investigated on the phenolic content and antioxidant activity of extracts from Tamarindus indica seed. The antioxidant activity of T. indica was determined by evaluating 1,1-Diphenyl-2-picrylhydrazyl (DPPH) scavenging activity, ferric reducing power assay (FRAP) and ascorbic acid equivalent content (AAC). The tested sample showed appreciable amounts of total phenolic contents (51.45-71.68 mg GAE/gm of dry extract), DPPH scavenging capacity (61.18-71.17%), IC50 values (98.30-248.60), reducing power (0.6377-0.7702) and total antioxidant capacity (22.75-43.80 AAE/gm) at different solvents and techniques. Current study data shown higher extract yields, phenolic contents, scavenging activity, reducing power and antioxidant activity using ethanol solvent compared to the respective acetone solvent. In addition, higher extract yields and other properties were obtained by hot extraction at 400C compared to the cold extraction at 260C. Present study suggests that ethanol as a solvent and hot extraction technique could be better to preserve the antioxidant properties of tamarind seed. http://dx.doi.org/10.5455/javar.2015.b103